2021
DOI: 10.1371/journal.pntd.0008822
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning model led design to experimentally test species thermal limits: The case of kissing bugs (Triatominae)

Abstract: Species Distribution Modelling (SDM) determines habitat suitability of a species across geographic areas using macro-climatic variables; however, micro-habitats can buffer or exacerbate the influence of macro-climatic variables, requiring links between physiology and species persistence. Experimental approaches linking species physiology to micro-climate are complex, time consuming and expensive. E.g., what combination of exposure time and temperature is important for a species thermal tolerance is difficult t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…While our study provides insight into the drivers of I. scapularis microbiome composition, our findings are necessarily associative and should help guide future more mechanistic studies (Rabinovich et al, 2021). These studies could include the controlled examination of host-seeking behaviour under varying environmental conditions using ticks that have been infected with pathogens of interest.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…While our study provides insight into the drivers of I. scapularis microbiome composition, our findings are necessarily associative and should help guide future more mechanistic studies (Rabinovich et al, 2021). These studies could include the controlled examination of host-seeking behaviour under varying environmental conditions using ticks that have been infected with pathogens of interest.…”
Section: Discussionmentioning
confidence: 93%
“…More broadly, mechanistic models have shown that non‐linear (i.e., threshold) effects of temperature are common in vector‐pathogen systems, but there have been few field studies that have investigated these effects (Mordecai et al, 2019; Rabinovich et al, 2021). Moreover, the statistical models used to investigate these nonlinear responses often struggle to separate temperature effects from covarying environmental factors and biotic factors (Mordecai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach imposes constraints on the types of data that can be effectively utilized for etiological inference [ 9 ]. In contrast, machine learning offers a promising avenue for addressing nonlinearity and interactions among variables [ 10 ], while also adeptly handling multi-dimensional datasets. Furthermore, the current prediction models for DF primarily rely on historical dengue case data.…”
Section: Introductionmentioning
confidence: 99%